The influence of various fertilizing methods on two new superior varieties of rice (Oryza sativa L.) in monsoon agroecosystem of Sulawesi - Muh. Afif Juradi; Titik Islami; Setyono Yudo Tyasmoro (Journal of Degraded and Mining Lands Management, 2017)
A research on the adaptation test of new superior varieties of rice and fertilization methods in monsoon agroecosystem in Sulawesi has been conducted in Baramamase Village, Walenrang subdistrict, Luwu Regency, South Sulawesi from February to, May 2016. The research location is located at an altitude of 13 m above sea level. The research aimed to find out the combination of treatments of new superior varieties of rice and location-specific fertilization methods to be developed. The experiment used completely randomized block design with four repetitions. The treatments use two varieties of rice consist of Ciherang and Inpari 30 each with fertilization methods of PUTS, Katam, Laboratory test and farmer pattern (as a comparison). Research result showed that treatment combination of Ciherang variety + fertilization method (PUTS, KATAM and laboratory test) increased the yield of harvested dry rice grain (PUTS of 171%, KATAM of 108%, and laboratory test 137%) compare to those of farmer pattern of 58%. Treatment of Inpari30 variety + fertilization method using PUTS, KATAM and laboratory test increased harvested dry grain yield of 85%, 72% and 100%, respectively, compare to those of farmer pattern of 46%. Ciherang variety is a superior rice variety and adaptive to specific environment thus it could be developed in the area of Luwu Regency, South Sulawesi.